A high temperature resistant copper-based methanol synthesis catalyst and preparation method thereof

By preparing nanosheet array carrier and embedded in Cu/Zn precursor, the problems of easy sintering and migration of active components in traditional catalysts at high temperatures are solved, and the catalyst's high sintering ability and long service life are achieved, and it is suitable for medium-pressure methanol synthesis.

CN115999551BActive Publication Date: 2025-03-18SINOPEC NANJING RES INST OF CHEM IND CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111224673.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-21
Publication Date
2025-03-18
Estimated Expiration
2041-10-21

AI Technical Summary

Technical Problem

Traditional Cu-ZnO-Al2O3-based catalysts are prone to sintering and inactivated at high temperatures, and the active components are unevenly migrated, resulting in a short catalyst service life.

Method used

By preparing a phthalinated water-aluminum stone nanosheet array carrier with uniform and highly dispersed structure, it is embedded in the Cu/Zn binary precursor, and a nanoarray-isolated high-temperature copper-based methanol synthesis catalyst is prepared after washing, filtration, drying, calcining and forming.

Benefits of technology

It improves the anti-sintering ability and thermal stability of the catalyst and extends its service life. It is suitable for synthesis gas producing methanol containing CO, CO2 and H2, and is especially suitable for large-scale methanol synthesis equipment for medium-pressure synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 385403DEST_PATH_IMAGE002
    Figure 385403DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The invention discloses a high temperature resistant copper-based methanol synthesis catalyst and a preparation method thereof. The specific operation of the preparation method is: firstly, a precipitant is dripped into an aluminum nitrate solution containing an auxiliary agent to obtain a pseudo-boehmite nanosheet array carrier, and then a Cu / Zn mixed salt solution and a precipitant are co-currently embedded between the nanosheet layer array carriers, and then washed, filtered, dried, calcined, and formed to obtain a high temperature resistant copper-based methanol synthesis catalyst isolated by a nano-array wall. The catalyst prepared by the method shown in the invention has the advantages of strong anti-sintering ability, good thermal stability, long service life, etc., and is suitable for preparing methanol from synthesis gas containing CO, CO2 and H2, and is particularly suitable for large-scale medium-pressure synthesis methanol devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst and a preparation method, in particular to a high-temperature resistant copper-based methanol synthesis catalyst and a preparation method, belonging to the technical field of catalysts. Background Art

[0002] As a basic chemical raw material, methanol is a bridge and link between coal chemical industry, natural gas chemical industry and petrochemical industry. It has great strategic significance for optimizing and adjusting the structure of my country's petrochemical industry, alleviating the contradiction between energy supply and demand, promoting the diversification and quality improvement of raw materials for chemical product production, and improving international market competitiveness. The development of the methanol industry depends to a large extent on the development and performance improvement of catalysts. In methanol production, many industrial indicators and operating conditions are determined by the properties of the catalyst. Since the first successful development of ICI, Cu-ZnO-Al2O3-based catalysts have always occupied an absolute dominant position in the market. The optimization and improvement of this series of catalysts have always received attention and attention from all countries, and their performance has been continuously improved and their service life has been continuously increased.

[0003] Cu-ZnO-Al2O3-based catalysts prepared by traditional processes have low melting points of active metal Cu, very low Tammann and Hüttig temperatures, and are prone to sintering and deactivation when used at high temperatures. To prevent catalyst sintering, it is necessary to prevent and slow down the migration of active centers and Ostwald ripening, and to fully isolate and fix the uniform and stable active center Cu as much as possible. In Cu-ZnO-Al2O3 catalysts, although the Al2O3 carrier plays a role in fixing active components and maintaining the catalyst structure, the Al2O3 obtained by the traditional coprecipitation method is usually amorphous, and its effect of spacing the active components of the catalyst and preventing the migration of active components is limited. If the Al2O3 carrier is given a certain morphology and constructed into a nanoarray with a specific arrangement, the uniform isolation of the active center of the catalyst can be achieved, and the problems of uneven distribution of active components and carriers, weak adhesion to the carrier, and migration and agglomeration of active components can be solved, the catalyst's anti-sintering ability can be improved, its heat stability can be increased, and the service life of the catalyst can be extended. While the array-isolated carrier plays the role of separating active components in physical space, the unobstructed channels between the array walls do not affect the contact between the active centers of the catalyst and the reaction substrates, which is beneficial to the improvement of catalytic activity. Summary of the invention

[0004] The purpose of the present invention is to provide a high-temperature resistant copper-based methanol synthesis catalyst and a preparation method, which breaks through the traditional copper-zinc-aluminum ternary methanol catalyst preparation method, especially the carrier preparation method, by preparing a pseudo-boehmite nanosheet array-type carrier with uniform structure and high dispersion, adjusting the density of the nanoarray, and embedding a Cu / Zn binary precursor between the nanosheet layer arrays, and then washing, filtering, drying, calcining, and molding to obtain a new type of nanoarray-isolated high-temperature resistant copper-based methanol synthesis catalyst.

[0005] In order to achieve the above technical objectives, the present invention proposes a high temperature resistant copper-based methanol synthesis catalyst and a preparation method thereof.

[0006] The invention provides a high temperature resistant copper-based methanol synthesis catalyst, wherein the catalyst main body consists of CuO, ZnO and Al2O3, and the components are measured by weight percentage, wherein the content of CuO is 45-70%, the content of ZnO is 15-30%, and the content of Al2O3 is 5-15%.

[0007] The preparation method of the high temperature resistant copper-based methanol synthesis catalyst provided by the present invention mainly comprises the following steps: firstly, a precipitant is dripped into an aluminum nitrate solution containing an auxiliary agent to obtain a pseudo-boehmite nanosheet array carrier slurry; then, a Cu / Zn mixed salt solution and the precipitant are co-precipitated and embedded between the nanosheet layer array carriers to obtain a nano-array isolated catalyst precursor slurry, and finally, a high temperature resistant copper-based methanol synthesis catalyst is prepared.

[0008] A typical preparation method of the catalyst of the present invention comprises the following steps: dripping a precipitant into a 0.5-2 mol / L aluminum nitrate solution containing an auxiliary agent under stirring conditions, controlling the precipitation temperature between room temperature and 50°C, the end point pH between 6.5 and 7.5, and the aging time between 30 and 120 minutes, so as to obtain a pseudo-boehmite nanosheet array carrier slurry; then co-precipitating a Cu / Zn soluble mixed salt solution and a precipitant solution at 60-75°C and under stirring conditions to embed the solution between the nanosheet layer array carriers, controlling the end point pH between 6.5 and 7.5, and the aging time between 30 and 240 minutes, so as to obtain a nano-array isolated catalyst precursor slurry; and washing, filtering, drying, calcining, and molding the slurry to obtain a nano-array isolated high temperature resistant copper-based methanol synthesis catalyst.

[0009] Furthermore, the auxiliary agent of the nanoarray sheet is at least one of zinc nitrate, zirconium nitrate, indium nitrate and gallium nitrate, and the ratio of auxiliary agent metal atoms to aluminum atoms is 1% to 15%.

[0010] The precipitant used to prepare the nanosheet array carrier is a mixed alkali solution.

[0011] The concentration of the mixed alkali is 0.5 mol / L to 2 mol / L.

[0012] The mixed alkali is sodium hydroxide plus any one of ammonia water, sodium bicarbonate, and sodium carbonate, or potassium hydroxide plus any one of ammonia water, potassium bicarbonate, and potassium carbonate; wherein the molar ratio of hydroxide to another alkali anion is 15:1-1:2.

[0013] The soluble Cu salt is at least one of copper nitrate and copper acetate, and the soluble Zn salt is at least one of zinc nitrate and zinc acetate; the total concentration of metal ions in the mixed salt is 0.5 mol / L to 2 mol / L.

[0014] The precipitant used for precipitation of the Cu / Zn mixed salt solution is at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate, and the concentration of the precipitant is 0.5 mol / L to 2 mol / L.

[0015] The high temperature resistant copper-based methanol synthesis catalyst prepared by the method of the present invention has a carrier which is a novel nano-array wall carrier with limited isolation capability, which can evenly separate and fix the Cu / ZnO active centers in a certain space, prevent the migration and agglomeration of Cu particles in the active centers, and slow down the sintering and growth of Cu particles during the reaction. Compared with the catalyst prepared by the traditional method, the catalyst prepared by the method of the present invention has the advantages of strong anti-sintering capability, good thermal stability, long service life, etc., and is suitable for methanol production from synthesis gas containing CO, CO2 and H2, and is particularly suitable for large-scale medium-pressure methanol synthesis equipment. DETAILED DESCRIPTION

[0016] The following examples are used to further illustrate the content of the present invention. The following examples are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0017] Example 1

[0018] Under stirring conditions, a 0.5 mol / L mixed alkaline solution (wherein the molar ratio of NaOH to ammonia water is 1:2) is dropped into a 0.5 mol / L aluminum nitrate solution containing zirconium nitrate (wherein the concentration of zinc nitrate is 0.075 mol / L), and the precipitation temperature is controlled to be room temperature, the end point pH is 6.5, and the aging time is 120 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are taken to prepare a Cu / Zn mixed salt solution (wherein Cu is 0.38 mol / L and Zn is 0.12 mol / L), and the Cu / Zn mixed salt solution and a 1 mol / L Na2CO3 / KHCO3 mixed solution are co-precipitated with the embedded nanosheet layer array carrier slurry under stirring conditions, and the precipitation temperature of this process is controlled to be 75°C, the end point pH is 7.5, and the aging time is 30 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat1.

[0019] Example 2

[0020] Under stirring conditions, a 2 mol / L mixed alkaline solution (wherein the molar ratio of NaOH to Na2CO3 is 3:2) is dropped into a 2 mol / L aluminum nitrate solution containing zinc nitrate (wherein the concentration of zinc nitrate is 0.1 mol / L), and the precipitation temperature is controlled at 45°C, the end point pH is 7.0, and the aging time is 45 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are prepared into a Cu / Zn mixed salt solution (wherein Cu is 1.5 mol / L and Zn is 0.5 mol / L), and the Cu / Zn mixed salt solution and a 2 mol / L Na2CO3 / NaHCO3 mixed solution are co-precipitated under stirring conditions to embed the nanosheet layer array carrier slurry, and the precipitation temperature of this process is controlled at 60°C, the end point pH is 6.8, and the aging time is 240 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat2.

[0021] Example 3

[0022] Under stirring conditions, a 1 mol / L mixed alkaline solution (wherein the molar ratio of KOH to KHCO3 is 15:1) is dropped into a 1 mol / L aluminum nitrate solution containing indium nitrate (wherein the concentration of indium nitrate is 0.08 mol / L), and the precipitation temperature is controlled to be room temperature, the end point pH is 7.5, and the aging time is 30 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are taken to prepare a Cu / Zn mixed salt solution (wherein Cu is 1.2 mol / L and Zn is 0.4 mol / L), and the Cu / Zn mixed salt solution and 1 mol / L K2CO3 solution are co-precipitated with the embedded nanosheet layer array carrier slurry under stirring conditions, and the precipitation temperature of this process is controlled to be 65°C, the end point pH is 7.2, and the aging time is 60 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat3.

[0023] Example 4

[0024] Under stirring conditions, a 1 mol / L mixed alkaline solution (wherein the molar ratio of NaOH to NaHCO3 is 10:3) is dropped into a 1.5 mol / L aluminum nitrate solution containing gallium nitrate (wherein the concentration of gallium nitrate is 0.015 mol / L), and the precipitation temperature is controlled to be room temperature, the end point pH is 7.0, and the aging time is 60 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are taken to prepare a Cu / Zn mixed salt solution (wherein Cu is 1.2 mol / L and Zn is 0.35 mol / L), and the Cu / Zn mixed salt solution and 1 mol / LNa2CO3 solution are co-precipitated under stirring conditions to embed the nanosheet layer array carrier slurry, and the precipitation temperature of this process is controlled to be 60°C, the end point pH is 7.0, and the aging time is 60 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat4.

[0025] Example 5

[0026] Under stirring conditions, a 1.5 mol / L mixed alkaline solution (wherein the molar ratio of KOH to ammonia water is 5:1) is dropped into a 1.5 mol / L aluminum nitrate solution containing zirconium nitrate (wherein the concentration of zirconium nitrate is 0.12 mol / L), and the precipitation temperature is controlled at 40°C, the end point pH is 7.0, and the aging time is 90 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are prepared into a Cu / Zn mixed salt solution (wherein Cu is 0.66 mol / L and Zn is 0.38 mol / L), and the Cu / Zn mixed salt solution and a 1 mol / L KHCO3 mixed solution are co-precipitated with each other under stirring conditions to embed the nanosheet layer array carrier slurry, and the precipitation temperature of this process is controlled at 65°C, the end point pH is 7.0, and the aging time is 45 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat5.

[0027] Example 6

[0028] Under stirring conditions, a 0.5 mol / L mixed alkaline solution (wherein the molar ratio of KOH to potassium bicarbonate is 2:3) is dropped into a 0.5 mol / L aluminum nitrate solution containing zinc nitrate (wherein the concentration of zinc nitrate is 0.10 mol / L), and the precipitation temperature is controlled at 30°C, the end point pH is 7.1, and the aging time is 80 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are prepared into a Cu / Zn mixed salt solution (wherein Cu is 1.0 mol / L and Zn is 0.5 mol / L), and the Cu / Zn mixed salt solution and a 1 mol / L K2CO3 / KHCO3 mixed solution are co-precipitated under stirring conditions to embed the nanosheet layer array carrier slurry, and the precipitation temperature of this process is controlled at 70°C, the end point pH is 7.1, and the aging time is 90 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat6.

[0029] Example 7

[0030] Under stirring conditions, a 2.0 mol / L mixed alkaline solution (wherein the molar ratio of KOH to potassium carbonate is 8:1) is dropped into a 2.0 mol / L aluminum nitrate solution containing indium nitrate (wherein the concentration of indium nitrate is 0.08 mol / L), and the precipitation temperature is controlled to be 50°C, the end point pH is 7.2, and the aging time is 70 minutes to obtain a pseudo-boehmite nanosheet array carrier slurry; Cu and Zn soluble salt solutions are prepared into a Cu / Zn mixed salt solution (wherein Cu is 1.1 mol / L and Zn is 0.6 mol / L), and the Cu / Zn mixed salt solution and a 1 mol / L NaHCO3 mixed solution are co-precipitated under stirring conditions to embed the nanosheet layer array carrier slurry, and the precipitation temperature of this process is controlled to be 75°C, the end point pH is 7.2, and the aging time is 120 minutes to obtain a nanoarray isolated catalyst precursor slurry; the slurry is washed, filtered, dried, calcined, and formed to obtain a nanoarray isolated high temperature resistant copper-based methanol synthesis catalyst Cat7.

[0031] Comparative Example

[0032] In the first step, under strong stirring, a 10% ammonia solution is added to a 1mol / L aluminum nitrate solution for neutralization precipitation reaction, the pH value of the neutralization end point is controlled to be 7.0, and the carrier is obtained after aging for 30 minutes. In the second step, Cu and Zn soluble salt solutions are measured to prepare a Cu / Zn mixed salt solution (Cu is 60g / L and Zn is 20g / L in the solution), and the Cu / Zn mixed salt solution is co-precipitated with a 1mol / L Na2CO3 solution under stirring conditions. The precipitation temperature of this process is controlled to be 65°C, the end point pH is 7.0, and aging is carried out under the same conditions for 30 minutes. After washing, filtering, drying, calcining, and molding, the copper-based methanol synthesis catalyst Cat8 is prepared.

[0033] Sample testing

[0034] Activity test: A micro-fixed bed continuous flow reactor was used, with a catalyst loading of 2 mL and a particle size of 16-40 mesh. The catalyst was reduced in a low hydrogen (H2:N2=5:95) atmosphere, with a programmed temperature increase (20°C / h) for 10 hours, and the temperature was raised to 230°C. The reducing gas was switched to the raw gas for activity test. The activity test conditions were a reaction pressure of 8.0 MPa and a space velocity of 10,000 h -1 , temperature 230℃, synthesis gas composition: H2:CO:CO2:N2 = 65:14:4:17 (v / v), after the reaction is stable for 2h, the liquid in the liquid collector is emptied and the timing is started. The collector is cooled by circulating water. After 2.5h, the collector liquid (crude methanol) is collected, weighed, and chromatographically analyzed. The calculated methanol space-time yield (STY) is the initial activity data. Then add 3 heat-resistant programs (thermal shock means). The gas source of the first program is switched to N2. After the catalyst is heat-treated at 350℃ for 5h, the activity after the first heat-resistant stage is measured under the above conditions; the gas source of the second program is switched to N2. After the catalyst is heat-treated at 380℃ for 5h, the activity after the second heat-resistant stage is measured under the above conditions; the gas source of the third program is switched to N2. After the catalyst is heat-treated at 400℃ for 5h, the activity after the third heat-resistant stage is measured under the above conditions. The methanol content in the liquid product was analyzed by Agilent-7890 gas chromatograph. The chromatographic conditions included a hydrogen flame ionization detector (FID), an HP-INNOWax column (column length 60m, inner diameter 0.32mm, wall thickness 0.5μm), programmed temperature, nitrogen as carrier gas, inlet temperature 250℃, constant pressure 10 psi, split mode 10:1, detection chamber temperature 300℃, hydrogen flow rate 30 mL / min, air flow rate 400 mL / min, tail flow rate 25 mL / min, and quantification by external standard method.

[0035] The activity test results are shown in Table 1, wherein samples cat1 to cat4 are prepared by the method of the present invention, and sample cat5 is a reference sample prepared by a traditional method.

[0036] Table 1 Activity test results

[0037]

[0038] It can be seen from Table 1 that the initial activity and the activity after heat resistance of the high temperature resistant copper-based methanol synthesis catalyst prepared by the method of the present invention are significantly higher than those of the sample prepared by the traditional process, and the catalyst activity decreases slowly after the three-stage heat resistance treatment, indicating that the catalyst sample prepared by the present invention has higher activity, better stability, and longer service life, can meet higher industrial production needs, is suitable for preparing methanol from synthesis gas containing CO, CO2 and H2, and is particularly suitable for large-scale medium-pressure methanol synthesis equipment.

[0039] It should be noted that the above is only a preferred embodiment of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A high temperature resistant copper-based methanol synthesis catalyst, characterized in that catalyst The main components are CuO, ZnO and Al2O3, and the weight percentage of each component is 45-70% for CuO, 15-30% for ZnO and 5-15% for Al2O3; The preparation method of the catalyst comprises the following steps: firstly adding a precipitant dropwise to a 0.5-2 mol / L aluminum nitrate solution containing an auxiliary agent under stirring conditions, controlling the temperature between room temperature and 50°C, the end point pH between 6.5 and 7.5, and the aging time between 30 and 120 minutes, to obtain a pseudo-boehmite nanosheet array carrier slurry; then preparing a Cu / Zn mixed salt solution prepared from soluble salts of Cu and Zn, co-precipitating the mixed salt solution and the precipitant under stirring conditions to embed between the nanosheet array carriers, controlling the precipitation temperature to 60-75°C, the end point pH between 6.5 and 7.5, and the aging time between 30 and 120 minutes, to obtain a nano-array isolated catalyst precursor slurry, and washing, filtering, drying, calcining, and molding the precursor slurry to obtain a nano-array isolated high temperature resistant copper-based methanol synthesis catalyst; The auxiliary agent is at least one of zinc nitrate, zirconium nitrate, indium nitrate and gallium nitrate.

2. The catalyst according to claim 1, characterized in that The ratio of additive metal atoms to aluminum atoms is 1%~15%.

3. The catalyst according to claim 1, characterized in that The soluble Cu salt is at least one of copper nitrate and copper acetate, the soluble Zn salt is at least one of zinc nitrate and zinc acetate, and the total concentration of metal ions in the mixed salt solution is 0.5 mol / L to 2 mol / L.

4. The catalyst according to claim 1, characterized in that The precipitant for preparing the nanosheet array carrier is a mixed alkali solution.

5. The catalyst according to claim 4, characterized in that The concentration of the mixed alkali solution is 0.5mol / L~2mol / L.

6. The catalyst according to claim 4 or 5, characterized in that The mixed alkali is sodium hydroxide plus any one of ammonia water, sodium bicarbonate, and sodium carbonate, or potassium hydroxide plus any one of ammonia water, potassium bicarbonate, and potassium carbonate, wherein the molar ratio of hydroxide to another alkali anion is (15:1) to (1:2).

7. The catalyst according to claim 1, characterized in that The precipitant used for precipitation of the Cu / Zn mixed salt solution is at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.

8. The catalyst according to claim 1 or 7, characterized in that The concentration of precipitant used for precipitation of Cu / Zn mixed salt solution is 0.5mol / L~2mol / L.

Citation Information

Patent Citations

  • Preparation method of high temperature resistant methanol catalyst

    CN106540700A

  • Preparation method for synthesizing methanol catalyst

    CN1891337A